2013
DOI: 10.7708/ijtte.2013.3(4).09
|View full text |Cite
|
Sign up to set email alerts
|

Study of Effect of Speed, Acceleration and Deceleration of Small Petrol Car on Its Tail Pipe Emission

Abstract: Pollution from vehicles is due to discharges like Carbon monoxide (CO), Carbon dioxide (CO 2), Hydrocarbon (HC) and Oxides of Nitrogen (NOx) through their tailpipe. Cars, being in dominant proportions (36.5%) in Indian traffic stream with small cars above 50% in total car proportions, are the main contributors to pollutants. Literature reveals that all factors being constant, at signalized intersection, car emission rates are the function of speed and acceleration. Since it is difficult to collect speed and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 13 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Moreover, several kinematic parameters such as average speed, instantaneous speed, and acceleration as well as driving condition characteristics, impact fuel consumption and thus emissions [16,45,67,68]. Previous works showed that higher levels of acceleration correspond to an increase in fuel consumption which leads to higher carbon monoxide (CO) and hydrocarbon (HC) emissions [45,69,70]. Though this driving pattern greatly impacts fuel consumption and therefore emissions, this study did not investigate this parameter.…”
Section: Fuel Consumption (C Day ) and Travelling Time (T P )mentioning
confidence: 97%
“…Moreover, several kinematic parameters such as average speed, instantaneous speed, and acceleration as well as driving condition characteristics, impact fuel consumption and thus emissions [16,45,67,68]. Previous works showed that higher levels of acceleration correspond to an increase in fuel consumption which leads to higher carbon monoxide (CO) and hydrocarbon (HC) emissions [45,69,70]. Though this driving pattern greatly impacts fuel consumption and therefore emissions, this study did not investigate this parameter.…”
Section: Fuel Consumption (C Day ) and Travelling Time (T P )mentioning
confidence: 97%
“…, n), AX ij is the original value of the jth index in the ith sample and AX ij is the treated value by the Equation (10). The weight of index (EW j ) can be calculated by EWM method using Equation (11).…”
Section: Confirmation Of Weight and Scoring Rulementioning
confidence: 99%
“…GPS can provide vehicle location directly and vehicle speed can be estimated based on the location. The acceleration and deceleration behaviour of drivers were studied using GPS in [10,11]. Video cameras were used to capture the drivers' facial expressions and eye movements to analyse the driving behaviour [12].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the EC EFs for all vehicles excluding transit in these two networks are not significantly different (P < 0.05). The EF comparison results for each pollutant are different, as the EF for each pollutant has a different association with traffic speed (Bokare and Maurya 2013).…”
Section: Contribution Of Trucks Transit Buses and Other Vehicles To Total Emissionsmentioning
confidence: 99%